Evaluation of the Relationship Between Relative Signal Intensity of Magnetic Resonance Images of Retrodiscal Tissue and Lateral Ptrygoid Muscle and Magnetic Resonance Imaging Findings - Hoda Banihashemi; Zahra Ghoncheh; Mehrdad Panjnoush; Farnosh Taghavi (Tehran University of Medical Sciences, 2012)
Background and Aims: Disc displacement is the most common temporomandibular joint disorder and magnetic resonance imaging (MRI) is the gold standard in its diagnosis. This disorder can lead to changes in signal intensity of magnetic resonance (MR). The purpose of this study was evaluation of correlation between relative signal intensity of MR images of retrodiscal tissue, superior and inferior head of lateral ptrygoid muscle with type of anterior disk displacement and condylar head flattening in patients with temporomandibular disorder (TMD). Materials and Methods: In this retrospective study, 31 MR images of patients who had anterior disc displacement were evaluated. After relative signal intensity measurement for retrodiscal tissue, superior and inferior head of lateral ptrygoid muscle, the correlation between relative signal intensity and type of anterior disc displacement was evaluated with repeated measure ANOVA test. In each of these 3 areas, t-test was used to compare the groups with and without condylar head flattening. Results: The correlation between relative signal intensity of MR images and type of anterior disc displacement in retrodiscal tissue, superior and inferior head of lateral ptrygoid muscle was not significant. There was also no statistically significant correlation between relative signal intensity of MR images and flattening of condylar head in retrodiscal tissue, superior and inferior head of lateral ptrygoid muscle (P>0.05). Conclusion: According to findings of this study, relative signal intensity of MR images in retrodiscal tissue, superior and inferior head of ptrygoid muscle is not a good predictor for type of anterior disc displacement and flattening of condylar head. It seems that this cannot be used as a diagnostic marker for TMD progression.